PENGARUH DISIPLIN KERJA, KOMPENSASI KERJA DAN LINGKUNGAN TERHADAP KINERJA KARYAWAN DI PT. BANK MANDIRI (PERSERO) TBK AREA MEDAN BALAIKOTA - Siketang, Ator; Simarmata, Ardyanti Yemima; Sibarani, Marion; Tarigan, Jenni (JURNAL GLOBAL MANAJEMEN, 2023)
This research embarks on an intricate exploration, delving into how ethical work practices, job remuneration, and the work environment synergize to mold employee performance at PT. Bank Mandiri (Persero) Tbk, specifically within the dynamic setting of Medan Balaikota. This study encompasses a comprehensive assessment of the various dimensions of work ethics, job remuneration, and the work environment, elucidating their profound impact on employee performance within the sphere of PT. Bank Mandiri (Persero) Tbk in the vibrant Medan Balaikota locale. Constructing the research inquiry revolves around dissecting the collective effect exerted by these independent variables on employee performance within the organizational domain. The formulated hypothesis posits that Variable (X) significantly steers the transformation of Variable (Y). Employing a comprehensive census sampling approach, a cohort of 40 participants was enrolled for the study. Data acquisition employed a meticulous fusion of diligent library research and hands-on field investigation techniques. Employing a quantitative descriptive methodology, this research harnessed the analytical prowess of multiple linear regression analysis, bolstered by the versatile SPSS (Statistical Package for Social Science) V23 software. The findings of the regression analysis unequivocally underscore that Variable (X) exerts a palpable impact on (Y). Ethical work practices conspicuously manifest a substantial influence on employee performance (t-value 1.401, significance < 0.05). Job remuneration emerges as a formidable influencer of employee performance (t-value 0.3540, significance < 0.05). Equally important, the work environment emerges as a pivotal shaper of employee performance (t-value 0.3670, significance < 0.05). The implications of the F-test are profound, with an F-value of 82.89 surpassing the critical F-table threshold of 2.87. Notably, the adjusted R Square value of 0.975 accentuates that Variable (X) elucidates a staggering 97.5% of the variability in Variable (Y). Drawing profound insights from these findings, the researcher unequivocally concludes that the independent Variable (X) wields a monumental influence over the dependent Variable (Y). Reflecting on these perceptive research discoveries, it is earnestly advised that the company's leadership meticulously scrutinizes the compensation framework, taking into cognizance the distinct attributes of employees and the intangible elements, in order to foster a motivational culture that propels employee performance.